Sumber Belajar dan Alat Permainan Edukatif untuk Anak Usia Dini - HM. Nasron HK; Jazila Anaka Putri; Elvis Winda; Nur Fitriya Zulkarnain (Bouseik: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
As a result of studying various materials, learning is a process or endeavor that each individual undertakes to bring about behavioral changes, whether in the form of knowledge, skills, attitudes, or positive values. To make the learning process enjoyable for children, a variety of learning resources and engaging educational activities are required. In early childhood, the goal of learning resources and educational game tools is to facilitate the implementation of engaging, focused, and high-quality learning activities for children. The availability of learning resources and educational game tools is crucial because it encourages children's enthusiasm, motivation, and interest in learning and exploring diverse information sources freely and in accordance with their interests. The method employed is a library research method or strategy, and data collection is conducted by studying and exploring a number of periodicals, books, and documents (both print and electronic), as well as other data and/or information sources regarded relevant to the research. Study. Parents and educators must utilize developmentally appropriate learning resources and educational play tools to leverage the potential of early childhood (AUD), according to the findings of this study.